Local Wisdom-Based Strategies for Shaping Children’s Discipline in Indonesian Early Education - Ardianti, Amelia Rizki; Setiaji, Calista Amalia; Darsinah; Wulandari, Murfiah Dewi (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study explores the implementation of local wisdom-based strategies in fostering discipline among children in early childhood education in the digital era. Conducted at PAUD Saymara, an early childhood education center in Central Java, Indonesia, the study investigates how local cultural values are integrated into discipline-building practices. Drawing on moral development theory (Kohlberg), character education theory (Lickona), and sociocultural theory (Vygotsky), this research employs a descriptive qualitative case study approach. Data were collected through participant observation, in-depth interviews with teachers and parents, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings identify seven key strategies: teacher role modeling, the use of local proverbs and traditional games, teacher–parent collaboration, structured play to reduce digital distractions, nature-based activities, positive reinforcement, and reflective practice. These strategies demonstrate that local wisdom functions not only as cultural content but also as a pedagogical framework that promotes self-regulation, empathy, and social responsibility. The study contributes a culturally responsive model of discipline formation and offers practical implications for educators and policymakers in designing contextually relevant character education programs.